Catalytic Pyrolysis of Low Density Polyethylene Using Cetyltrimethyl Ammonium Encapsulated Monovacant Keggin Units C19H42N4H3(PW11O39) and ZSM-5 - Madeeha Batool; Asma Tufail Shah; Muhammad Imran Din; Baoshan Li (Journal of Chemistry)
The effect of the catalysts on the pyrolysis of commercial low density polyethylene (LDPE) has been studied in a batch reactor. The thermal catalytic cracking of the LDPE has been done using cetyltrimethyl ammonium encapsulated monovacant keggin units (C19H42N)4H3(PW11O39), labeled as CTA-POM and compared with the ZSM-5 catalyst. GC-MS results showed that catalytic cracking of LDPE beads generated oilier fraction over CTA-POM as compared to ZSM-5. Thus, the use of CTA-POM is more significant because it yields more useful fraction. It was also found that the temperature required for the thermal degradation of LDPE was lower when CTA-POM was used as a catalyst while high temperature was required for degradation over ZSM-5 catalyst. Better activity of CTA-POM was due to hydrophobic nature of CTA moiety which helps in catalyst mobility and increases its interaction with hydrocarbons.